Identification of proteins in Sporothrixschenckiisensu stricto in response to oxidative stress induced by hydrogen peroxide. - Ruiz-Baca, Estela; Leyva-Sánchez, Hilda; Calderón-Barraza, Bertha; Esquivel-Naranjo, Ulises; López-Romero, Everardo; López-Rodríguez, Angélica; Cuéllar-Cruz, Mayra (Revista Iberoamericana de Micologia, 2019)
Abstract Background Sporotrichosis is a fungal infection caused by the Sporothrix schenckii complex. In order to colonize the host, the pathogen must neutralize the reactive oxygen species produced by the phagocytic cells during the respiratory burst. Little is known about these mechanisms in S. schenckii. Aims To identify the proteins differentially expressed after the exposure of S. schenckii sensu stricto to different concentrations of H 2 O 2. Methods Yeast cells of S. schenckii sensu stricto were exposed to increasing concentrations of H 2 O 2. Proteins differentially expressed in response to oxidative stress were analyzed using two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and identified by MALDI-MS/MS. RT-PCR assays were performed to evaluate the transcription of genes of the identified proteins. Results Concentrations of H 2 O 2 as high as 800 mM allowed cell growth, and 200 mM and 400 mM were selected for comparative analysis by 2D-PAGE. This analysis revealed at least five differentially expressed proteins, which were identified as heat shock 70 kDa protein (Hsp70), chaperonin GroEL, elongation factor 1-β (EF1-β), a hypothetical protein, and mitochondrial peroxiredoxin (Prx1). RT-PCR revealed that the transcription of the genes coding for some of these proteins are differentially regulated. Conclusions Based on these results, it is proposed that these proteins may be involved in the resistance of S. schenckii to oxidative stress, and play an important role in the fungus survival in the host.